Dental service disparities in Canada: A Saskatoon, Saskatchewan case study. (26th July 2016) - Jones, Marina; Shah, Tayyab; Hayes, Alyssa; Uswak, Gerry; Bell, Scott
Abstract : Oral health is an intrinsic component of overall health and wellbeing. However, in Canada oral health care (other than emergency, hospital‐based services) is not covered by the Canada Health Act and is delivered primarily on a fee‐for‐service basis. This study explores the urban arrangement of dental services in comparison with other Primary Health Care services (in this case, family physicians) and further, determines the association between access to dental services and socio‐economic variables. A GIS‐based spatial accessibility method was used to calculate the neighbourhood access score for both dental and family physician services within Saskatoon, Saskatchewan. Spatial analysis and spatial statistical methods were applied to determine the relationship between dental access score and socio‐economic variables. A best‐fit linear regression model was identified using a forward step‐wise approach. Next, to reduce the spatial autocorrelation present in the linear model, a spatial lag regression model that includes a spatially lagged dependent variable, spatial weight matrix (queen contiguity, row‐standardized) was estimated. Three explanatory variables (lone parent, home ownership, and dwellings needing major repairs) were found to be associated with the access to dental services. This study demonstrates the power of looking beyond the simple arrangement of health care services to highlight poorly served neighbourhoods in urban settings. Les disparités dans l'offre de services dentaires au Canada : une étude de cas de Saskatoon, Saskatchewan: La santé buccodentaire fait partie intégrante de la santé et du bien‐être au sens large. Cependant, au Canada les soins de santé buccodentaire (autres que les services d'urgence dans les milieux hospitaliers) ne sont pas assurés par la Loi canadienne sur la santé et sont offerts surtout selon le principe de la rémunération à l'acte. L'exploration menée dans le cadre de cette étude porte sur la structuration urbaine des services dentaires comparativement avec d'autres services de soins de santé de première ligne (dans ce cas, les médecins de famille) et permet d'établir, en outre, l'existence d'une association entre l'accès aux services dentaires et les variables socio‐économiques. Le recours aux SIG pour la modélisation de l'accessibilité a servi à estimer un indicateur d'accès aux services dentaires et aux médecins de famille par quartier sur le territoire de Saskatoon, Saskatchewan. L'utilisation de l'analyse spatiale et des méthodes de statistiques spatiales a fait ressortir la relation entre l'indicateur d'accessibilité aux services dentaires et les variables socio‐économiques. Un modèle de régression linéaire ordinaire est obtenu avec une approche ascendante par étapes. Ensuite, un modèle autorégressif avec décalage spatial permet de contrôler l'effet d'autocorrélation spatiale. Il comporte une variable dépendante spatialement décalée et une matrice de pondération spatiale (contiguïté de type reine, standardisé par ligne). On constate une association entre l'accès aux services dentaires et trois variables explicatives (monoparentalité, taux de propriété, et logement nécessitant des réparations majeures). L'étude a permis de constater l'intérêt de dépasser la question de la structuration des services de soins de santé pour mieux caractériser les quartiers mal desservis en milieu urbain. Key Messages: This intra‐urban analysis of spatial accessibility to dental services highlights poorly served municipalities. The dental access score is found to be associated with the following socio‐economic variables: lone parent, home ownership, and dwellings needing major repairs.